Enhanced corrosion protection of reinforcement steel with nanomaterial incorporated fly ash based cementitious coating. (15th March 2021) - Rooby, Divya Rachel; Kumar, T. Nanda; Harilal, Manu; Sofia, S.; George, R.P.; Philip, John
Highlights: A novel cementitious coating for rebar is developed with flyash and nanoparticles (NP's). Behavior of NP's like ZrO2, SiO2, CaCO3 against corrosion was compared. Electrochemical tests showed superior performance for nano-modified coatings. Cementitous coating with Nano-ZrO2 exhibited better barrier property than other NP's. Accelerated hydration and pore-filling by NP's resulted in enhanced permeation resistance. Abstract: This work evaluated the performance of a novel nanophase modified fly ash based cement polymer coating over steel reinforcements in a corrosive environment. Five types of coatings were prepared with 100 wt. % Ordinary Portland Cement (CC), OPC replaced with 40 wt. % fly ash (CF), and CF admixed with 2 wt. % nano-CaCO3 (CFC), nano-SiO2 (CFS) and nano-ZrO2 (CFZ). Electrochemical studies were carried out under exposure to chlorides and the long term performance was evaluated by impressed voltage test. The microstructure of the developed coatings and chemical composition of corrosion products were analyzed using SEM, XRD, and LRS. The instantaneous corrosion rates of CFC, CFS, and CFZ coated rebars were found to be notably lower than CF coated rebars. The accelerated studies using impressed voltage test indicated a significantly longer initiation time for cracking in nanomaterials incorporated coatings than the conventional cement polymer coating. The evaluation of electrochemical parameters like open circuit potential, corrosion current, and polarization resistance showed that the addition of nano-ZrO2 significantly enhanced the corrosion performance of cementitious coatings as compared to other nanomaterials owing to its better dispersibility, without aggregation in cementitious product, which was further confirmed from the particle size distribution measurement using dynamic light scattering technique. The XRD patterns and laser Raman spectra results confirm negligible corrosion products on CFZ coated rebars. The visual inspection of rust formation and weight loss measurements of CFZ coated rebars, subjected to salt spray and chemical resistance tests corroborated its long term durability in chloride-rich environment. Our results suggest the important benefits of nanomaterial incorporated fly ash cementitious coating on rebars in corrosion protection.